Reusable polycaprolactone based sorbents with different cross-linking densities for the removal of organic pollutants - Uzunok, Simge; Sonmez, Hayal Bulbul (Elsevier Sci Ltd, 2023)
Organic synthetic sorbent materials are commonly preferred for the cleaning of petroleum-based pollution. These sorbents show hydrophobic properties thanks to their cross-linked network structures. Due to their cross-linked structure, sorbents do not dissolve in solvents and their hydrophobic nature enables them to collect organic liquids from the water surface selectively. In addition to these features, the sorbents can reach their absorption capacity quickly, can be reused, and do not sink in the water, making polymeric sorbents an ideal material for cleaning petroleum-derived impurities. In this paper, polycaprolactone (PCL) based sorbents were synthesized by using PCL monomer and different silane-based cross-linkers. Within the scope of the article, the effect of the degree of cross-linking on sorption capacity, sorption-desorption rate, and sorption of organic liquids from the water surface has been investigated. Characterization of the polymeric sorbents was performed by using Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), and optical microscope. The obtained sorbents show high and quick absorption properties in organic solvents in the range of 5.45-51.00 g.g(-1), and they can be used for at least ten cycles without any loss of capacity.
Keywords: Polycaprolactone; Sorbents; Reusability; Oil spills; Selectivity